Ikaros (IKZF1) alterations and minimal residual disease at day 15 assessed by flow cytometry predict prognosis of childhood BCR/ABL-negative acute lymphoblastic leukemia - Volejnikova, Jana; Mejstrikova, Ester; Dörge, Petra; Meissner, Barbara; Zimmermannova, Olga; Svojgr, Karel; Stanulla, Martin; Cario, Gunnar; Schrappe, Martin; Stary, Jan; Hrusak, Ondrej; Trka, Jan; et al. (Pediatric blood & cancer, 2013)
BACKGROUND: Recently, several studies have demonstrated a negative prognostic impact of Ikaros (IKZF1) gene alterations in acute lymphoblastic leukemia (ALL). However, controversies still exist regarding the impact of IKZF1 in current treatment protocols. PROCEDURE: We simultaneously detected IKZF1 gene deletions by multiplex ligation-dependent probe amplification and gene expression of IKZF1 isoforms in 206 children with BCR/ABL-negative ALL treated with ALL IC-BFM 2002 protocol, in which risk stratification was not based on minimal residual disease (MRD), and validated the results on a cohort of 189 patients treated with MRD-directed ALL-BFM 2000 protocol. RESULTS: Deletion of IKZF1 was present in 14 of 206 (7%) ALL IC patients. Interestingly, gene expression did not completely correlate with the deletion status in either cohort. Deletions were not always reflected in the gene expression of dominant-negative isoforms, and conversely, 7 of 395 (2%) non-deleted cases overexpressed dominant-negative isoform Ik6. IKZF1 deletions significantly affected event-free survival (EFS) of the ALL IC cohort (41 ± 14% vs. 86 ± 3%, P < 0.0001). Regarding IKZF1 isoforms, only Ik6 overexpression had negative prognostic impact (EFS 50 ± 16% vs. 85 ± 3%, P = 0.003). In multivariate analysis, which included ALL IC risk criteria, flow-cytometric MRD and IKZF1 alterations, day 15 MRD and IKZF1 deletion status displayed an independent prognostic impact. CONCLUSIONS: We show that MRD-directed treatment diminishes prognostic impact of IKZF1 alterations. However, IKZF1 status alone or combined with day 15 flow cytometry can significantly improve risk stratification within BFM protocols at centers that do not perform antigen-receptor-based MRD monitoring.
Keywords: Prognosis; přežití bez známek nemoci; předškolní dítě; Disease-Free Survival; Humans; Neoplasm, Residual; reziduální nádor; bcr-abl fúzní proteiny; prognóza; Risk Factors; mužské pohlaví; Flow Cytometry; transkriptom; Child, Preschool; Precursor Cell Lymphoblastic Leukemia-Lymphoma; rizikové faktory; průtoková cytometrie; Fusion Proteins, bcr-abl; ženské pohlaví; akutní lymfatická leukemie; lidé; Transcriptome; dítě; Child; transkripční faktor Ikaros; Male; Ikaros Transcription Factor; Female